2001
DOI: 10.1177/01939450122045500
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Experience of Male Infertility

Abstract: The purpose of this study was to describe the lived experiences of Chinese men who were diagnosed as infertile. Thirty men who had experienced infertility were interviewed in or near the clinic of a large general teaching hospital located in Taiwan. The interviews were analyzed using content analysis. Five categories were generated from the interview data: emotional response after hearing the diagnosis; seeking possible explanations for the diagnosis; using alternative treatments other than those of Western me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…In ‘Shang han lun’ and ‘Jin kui yao lue’, the representative classical textbook of traditional Chinese medicine, we cannot find descriptions about other significant clinical efficacies of herbal drugs on improving fertile function other than Unkei‐to. In addition to our reports, several recent investigators, however, demonstrated that some herbal medicines can play a significant role in improving the human fertility rate 4,24,50–54 …”
Section: Conclusion and Recommendationssupporting
confidence: 55%
“…In ‘Shang han lun’ and ‘Jin kui yao lue’, the representative classical textbook of traditional Chinese medicine, we cannot find descriptions about other significant clinical efficacies of herbal drugs on improving fertile function other than Unkei‐to. In addition to our reports, several recent investigators, however, demonstrated that some herbal medicines can play a significant role in improving the human fertility rate 4,24,50–54 …”
Section: Conclusion and Recommendationssupporting
confidence: 55%
“…Based on this background, infertile men reportedly suffered from a feeling of helplessness, a humiliating sense of shame, and reduced reproductive function (Asazawa, 2012). The stress and frustration of infertile men because of the non-continuity of the family line and infertility onset also have been reported previously (Lee & Chu, 2001). In Japan, there is a normative model that "reproduction is a female task," as well as a culture that men's infertility should not be known.…”
Section: Providing Care To Maintain the Quality Of Life Of Male Patientsmentioning
confidence: 68%
“…In general, shame about the diagnosis constrained disclosure to anyone apart from their wives. 75 Malik and Coulson 76 investigated the extent to which the internet was used as a resource for information and emotional support, postulating that availability, accessibility and anonymity would make it especially acceptable to men. They undertook a thematic analysis of 728 messages posted by men on an online infertility support group message board.…”
Section: Male Experiences Of Infertility Treatmentmentioning
confidence: 99%